Pertumbuhan dan Produksi Tanaman Terong pada Berbagai Media Tanam dan Pemberian PGPR (Plant Grownth Promoting Rhizobacteria) - Abdul Haris; Baktiar Ibrahim; Abdul Akbar; Rismayanti (Journal Galung Tropika, 2024)
This study aims to determine the effect of a combination of planting media, PGPR, and the interaction between the two treatments on the growth and production of eggplant plants. This study used a Randomized Group Design factorial pattern of 2 factors. The first factor is the use of planting media composition with three levels of treatment, and the second factor is the dosing of PGPR plants with 4 levels and 12 treatment combinations. Each combination was repeated 3 times, resulting in 36 experimental units. The results showed that the planting media composition of soil + rice husk + manure fertilizer significantly affected the parameters of plant height and tended to be better on the parameters of flowering age, number of fruits, fruit diameter, and fruit weight. The application of PGPR at a dose of 20 ml/liter significantly affected the parameters of the number of leaves and the number of fruits. It tended to be better on the parameters of fruit length. The interaction between the dose of PGPR and the composition of planting media had no significant effect on all parameters of eggplant plants.